Energy, exergy and economic analysis of phase change material based hybrid photovoltaic thermal systems / Md. Shouquat Hossain - Md. Shouquat , Hossain (2018)
Efficient extraction and conversion of energy is a burning issue in today’s world. Photovoltaic (PV) technology suffers from the major drawback of poor energy conversion efficiency that is further worsen by overheating of the module. Hybrid photovoltaic thermal (PV/T) collectors have bring about a notable change in this technology by enabling the extraction of both electricity and heat from the same module, thereby improving the overall efficiency. However, there are some technical challenges with these devices that obstacles their wide-scale application. The major shortcoming of conventional water based PV/T collectors is that their operation is limited only in daytime. Use of phase change materials (PCM) in PV/T collectors as an intermediate thermal storage media offers a promising solution to this problem by storing large amount of heat. The aim of this research work is to design and develop a PV/T-PCM system with self-cleaning facility (PV/T-PCM-SC) and evaluate its performance through energy, exergy and economic analysis. The thermal collector of the PV/T is a novel parallel serpentine pipe flow channel that extracts maximum heat from the PV module. Lauric acid PCM contained in leak-proof aluminum foil packets are placed around the flow channel allowing extended period of thermal storage. The PV glass cover is equipped with a self-cleaning mechanism to ensure well transmittance of solar irradiation allowing more energy to intercept. In order to make comparative performance study with a reference PV module, three systems, viz., PV/T-only, PV/T-PCM and PV/T-PCM with self-cleaning has been developed. Energy analysis, which is based on the first law of thermodynamics, gives the maximum thermal efficiency of PV/T-only, PV/T-PCM and PV/T-PCM with self-cleaning system as 74.62%, 87.72% and 77.60%, respectively. On the other hand, a second law analysis of all of the systems reveals that maximum exergy efficiency of PV/T-only, PV/T-PCM and PV/T-PCM with self-cleaning system are 12.98%, 12.19% and 12.68%, respectively. Electrical performance of all the three systems has also been analyzed and it was observed that PV/T-only, PV/T-PCM and PV/T-PCM with self-cleaning system are 10.46%, 11.08% and 11.91% respectively. An economic analysis of the proposed system has also been carried out with a view to examine the feasibility of its commercialization. It may be concluded from the analysis that commercialization of PV/T-PCM with self-cleaning system is worthwhile and with mass production, it will become more cost effective. A PV/T-PCM system with novel parallel serpentine pipe thermal collector has been developed that not only incorporates PCM thermal management, but also self-cleaning facility to ensure improved performance. To the best of knowledge, the proposed PV/T-PCM system with self-cleaning approach is first of its kind and deserves commercial application, at least, on household scale. This system can provide both electricity and heat to the households of remote areas that are out of the reach of electricity grid that will contribute to curb power crisis to a good extent. The provision of self-cleaning system makes it excellent choice for applications in coastal regions.